WAYS TO DEVELOP CREATIVE THINKING IN GEOGRAPHY EDUCATION - Feruza Asrorovna Khamroyeva; Zarina Sulaymonovna Sunnatillayeva (Research Focus International Scientific Journal, 2025)
This article discusses the importance of creative thinking, the “Six Thinking Hats” method aimed at developing students’ ability to analyze problems from various perspectives and enhance their creative thinking, as well as the effectiveness of applying this method in geography lessons. The article analyzes how the method is implemented in the educational process, its role in developing students’ thinking abilities, and its methodological aspects.